2008
DOI: 10.1007/s00520-007-0383-z
|View full text |Cite
|
Sign up to set email alerts
|

Oral moxifloxacin or intravenous ceftriaxone for the treatment of low-risk neutropenic fever in cancer patients suitable for early hospital discharge

Abstract: These results suggest that MASCC is a valid and useful tool to select patients for ambulatory treatments and that oral moxifloxacin monotherapy is safe and effective for the outpatient treatment of cancer patients with low-risk neutropenic fever.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
0
3

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 30 publications
(31 reference statements)
2
27
0
3
Order By: Relevance
“…The success rate of the treatment was 84% (63 of 75 episodes), and 71 of 75 episodes (95%) were resolved without hospitalization. Several studies evaluating the use of oral antibiotics in the outpatient management of low-risk FN have reported treatment success rates of 77-95% (10,(14)(15)(16)(17), which is consistent with the results of the present study.…”
Section: Discussionsupporting
confidence: 82%
“…The success rate of the treatment was 84% (63 of 75 episodes), and 71 of 75 episodes (95%) were resolved without hospitalization. Several studies evaluating the use of oral antibiotics in the outpatient management of low-risk FN have reported treatment success rates of 77-95% (10,(14)(15)(16)(17), which is consistent with the results of the present study.…”
Section: Discussionsupporting
confidence: 82%
“…Since these studies were conducted gatifloxacin has been withdrawn from clinical use. Moxifloxacin has also been evaluated for prophylaxis as well as empiric therapy in febrile neutropenic patients [2,23,27]. Chamilos and colleagues treated 54 patients with solid and hematologic malignancies with oral, outpatient moxifloxacin [2].…”
Section: Discussionmentioning
confidence: 99%
“…These trials showed promising results but are no longer pertinent since gatifloxacin has been withdrawn from clinical use due to toxicity issues. Moxifloxacin has also been evaluated in this setting with response rates in the 80-91% range [2,23]. We have conducted a pilot study of oral outpatient moxifloxacin monotherapy in low-risk febrile neutropenic patients and would like to add our experience to that which has already been published.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…with oral treatment for neutropenia in cancer patients, but reported no methodological details of the parent studies. 22,[48][49][50][51] In the remaining five trials, details of randomisation, allocation concealment and blinding (especially in relation to assessment of outcome measures) were poorly reported. 52 The five case-control studies (three of which were retrospective) rated low for potential bias (median 8/9; range 6-9).…”
Section: Risk Of Bias Within Studiesmentioning
confidence: 99%